Ways of Using Audiovisual Materials in the Process of Teaching a Foreign Language (Journal of Pedagogical Inventions and Practices, 2023)
This article analyzes the effective methods of "Formation of socio-cultural competence of academic lyceum students using authentic video materials in foreign language teaching". Learning a foreign (non-native) language is challenging for any language learner. In order to overcome such difficulties, at first, the issues offormation of communicative competence of language learners were considered. Also, in the process of language teaching, the audio and video materials provided by the teacher to language learners of different ages were sorted step by step. Video materials are important in language teaching. The ability of students to learn the language increases by remembering the thoughts, psycho-emotional state, facial expressions, and gestures of the speaker in the audio and video materials. In the process of using such materials, a language learner may not fully understand the speaker from the video material, but can guess or partially understand the speaker's speech from his gestures and facial expressions. Through such materials, the language learner gradually develops the ability to learn the language. According to the results of the study, compared to the information provided only by voice, the information presented with the help of audio videos helps language learners to understand the reality as a whole. Audiovisual, thematically adapted to the audience of language learners it is possible to increase their communicative competence with the help of materials.